A holistic approach to manta ray conservation in the Papuan Bird's Head Seascape: Resounding success, ongoing challenges. (March 2022) - Setyawan, Edy; Erdmann, Mark; Gunadharma, Nikka; Gunawan, Tiene; Hasan, Abdi; Izuan, Muhamad; Kasmidi, Meidiarti; Lamatenggo, Yusdi; Lewis, Sarah; Maulana, Nugraha; Mambrasar, Ronald; Mongdong, Meity; et al.
Abstract: Despite a precipitous decline in global populations of sharks and rays over the past fifty years due to overfishing, and increasing concerns over the conservation status of manta and devil rays worldwide, manta ray populations in Raja Ampat in the Papuan Bird's Head Seascape of Indonesia are seemingly thriving. Reef manta rays ( Mobula alfredi ) in particular are abundant and have higher rates of pregnancy than have been recorded elsewhere in the Indo-Pacific, and have demonstrated a significant population increase over the past decade of monitoring. Here we document two decades' of conservation efforts in the Bird's Head Seascape (BHS) which, when considered in their entirety, represent an organically-developed, holistic approach to manta ray conservation that has demonstrated compelling evidence of success despite ongoing challenges. We provide detailed insights on the adaptive, continuously evolving approach used for manta ray conservation in the BHS in order that this approach might inform similar efforts towards elasmobranch conservation in other areas of the developing tropics.